A checklist of Cicadidae (Insecta: Hemiptera) from Cambodia, with two new species and a key to the genus Lemuriana - Lee, Young June (Zootaxa, 2010)
This paper provides the first faunal checklist of Cicadidae (Insecta: Hemiptera) from Cambodia, comprising 25 species belonging to 16 genera. Two new species, Tanna kimtaewooi sp. nov. and Lemuriana cambodiana sp. nov., are described. Platypleura mira Distant, 1904, Chremistica moultoni Boulard, 2002, Cryptotympana recta (Walker, 1850), Pomponia subtilita Lee, 2009, Purana parvituberculata Kos & Gogala, 2000, Orientopsaltria padda (Distant, 1887), and Platylomia malickyi Beuk, 1998 are newly added to the cicada fauna of Cambodia. Megapomponia imperatoria (Westwood, 1842), which was erroneously recorded due to misidentification, is removed from the fauna. Information on geographic distributions is also provided. A key to the species of the genus Lemuriana Distant 1905 is provided.